Desenvolvimento de imunossensor baseado na imobilização de anticorpo monoclonal em fibroína da seda para diagnóstico rápido da cisticercose bovina - Oliveira, Josy Campanhã Vicentini de [UNESP] (2014)
Bovine cysticercosis is a cosmopolitan zoonosis and very widespread in the Brazilian beef cattle. Cysticercosis usually occurs in developing countries, where poor sanitation and bad raising cattle practices allows the contamination of the pasture and water with human feces containing eggs. The financial losses are due to condemnation or treatment (salting or freezing) of infected carcasses, depending on the intensity of infection. Diagnosis of bovine cysticercosis is routinely done during slaughter by meat inspection of carcasses and incisions in predicted sites of muscles such as tongue, masseter, heart and diaphragm. Thus, in order to promote the ante-mortem diagnosis and allow appropriate treatment of infected animals, many studies have been performed using techniques to detect antibodies or antigens in bovine serum. ELISA using monoclonal antibodies (MAbs) for the detection of circulating antigen (Ag-ELISA) has been studied, but presents low sensitivity in animals with low parasite burden, and allows its realization only in well-equipped laboratories. The use of biosensors in medicine has grown in recent years, allowing detection and quantification of numerous metabolites, such as immobilization matrix having the most diverse biopolymers such as chitosan and silk fibroin. Immunosensors are biosensors which biochemical response is related to antigen-antibody interaction and can be used to detect antibodies or antigens, and has been tested for diseases diagnosis. In this research, we developed the first immunosensor for bovine cysticercosis diagnosis, produced with layer-by-layer (LbL) films containing a monoclonal antibody against crude Taenia saginata metacestode antigens (TAEB) and silk fibroin (SF) immobilized. Immunosensor showed to be a promising tool for further application in the ante-mortem bovine cysticercosis diagnosis